Modeling of aluminum erosion by neutral particles in dedicated EAST experiments using the 3D-GAPS code. (1st June 2023) - Shi, X.Z.; Ding, R.; Matveev, D.; Mu, L.; Liu, N.X.; Xie, H.; Xu, G.L.; Chen, J.L.
Abstract: To evaluate the erosion effects of charge exchange (CX) neutrals on first wall materials, aluminum (Al) coated samples installed in a cylindrical sleeve were exposed to EAST plasmas with the Material and Plasma Evaluation System (MAPES). The 3D-GAPS code was firstly used to simulate the dedicated experiments with the neutral energy spectrums measured by the Low Energy Neutral Particle Analyzer located at the MAPES. The modeled Al erosion rates with isotropic angular distributions for incident D neutrals are consistent with the measured erosion thicknesses of Al layer by Rutherford backscattering spectrometry before and after the plasma exposure. The effects of neutral reflection coefficients and the heights of cylindrical sleeve on material erosion are also studied. The measured material erosion rate by CX neutrals in EAST verified by the modeling can help to us understand the effects of neutrals on first wall erosion, which is an important erosion process in future fusion reactors.